2022
DOI: 10.24191/ajue.v18i1.17172
|View full text |Cite
|
Sign up to set email alerts
|

REV-OPOLY: A Study on Educational Board Game with Web-based Augmented Reality

Abstract: The use of technology in education is believed to enhance students’ learning experience. Technology such as Augmented Reality (AR) is increasingly used in the classroom through the use of gamification. This study aims to examine students' experience in using a board game with web-based Augmented Reality named REV-OPOLY in their learning. REV-OPOLY’s theme is on the emerging technology revolution concepts where in this board game, players can buy, rent and sell technologies through question cards to gain the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Johnson et al (2021) evaluated the effectiveness of a free online financial educational program where financial knowledge improvement was significant. Nordin et al (2022) investigated AR gamification technology use; 93% of the students reported that it was a better learning media.…”
Section: Motivation To Engage the Contentmentioning
confidence: 99%
“…Johnson et al (2021) evaluated the effectiveness of a free online financial educational program where financial knowledge improvement was significant. Nordin et al (2022) investigated AR gamification technology use; 93% of the students reported that it was a better learning media.…”
Section: Motivation To Engage the Contentmentioning
confidence: 99%
“…Additionally, educational board games have proven highly effective for teaching, outreach, and increasing awareness in STEM disciplines (Chiarello & Castellano, 2017). Board games have also been effectively employed in different fields as an instructional tool that fosters learning, such as management courses (Nordin & Omar, 2022), marine science (Lin et al, 2019), complex scientific concepts (Chiarello, 2015), mathematics (Hawes et al, 2020), chemistry (Tsai et al, 2020), language (Poole et al, 2019), and computational thinking (Kuo & Hsu, 2020).…”
Section: Introductionmentioning
confidence: 99%